PENINGKATAN PROSES PEMBELAJARAN TEMATIK TERPADU TEMA TEMPAT TINGGALKU KELAS IV SDN 14 MENGGUNAKAN PENDEKATAN SCIENTIFIK - EVAYANTI, DASLINA (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
Abstract The purpose of this research was to describe the improvement of the integrated thematic teaching and learning process on My hometown theme by using scientific approach in class IV of SDN 14 V Koto Timur. This was a Classroom Action Research which applied both quanlitative and quantitative approaches. The subject of the research was 30 students in class IV. The result of the research revealed that from the first cycle to the second one, the score of the Lesson Plan increased from 71,6% to 92,2% and the quality of the learning process increased from 76,1% to 90,4%. Thus, scientific approach could increase the integrated thematic teaching and learning process in class IV of SDN 14Kata kunci: proses pembelajaran, tematik,pendekatan scientifik